A comparative study of haemocytes in three cyclorrhaphous dipteran flies. (15th August 2014) - Pal, Ruchita; Kumar, Krishna
Abstract : The larval haemolymph of three cyclorrhaphous dipteran flies, Sarcophaga ruficornis Fab., Musca domestica L. and Chrysomya megacephala Fab., possesses five different types of haemocytes: prohaemocytes; plasmatocytes; granulocytes; spherulocytes; oenocytoids. In addition, vermicytes are found in the haemolymph of S. ruficornis and adipohaemocytes in the haemolymph of M. domestica . The total haemocyte counts in the three dipteran flies show an increasing trend throughout the larval stage, attaining a peak value in the freshly formed white puparium stage and declining thereafter. The differential haemocyte count shows a decline in the number of prohaemocytes with an increase in the number of plasmatocytes, granulocytes and spherulocytes.